Factors that Influence The Use of BRI Mobile Banking on UMS Students - Krismono, Abdi; Mustofa, Rochman Hadi (Proceedings International Conference on Education Innovation and Social Science, 2024)
Fintech or financial technology affects the digital financial sector where this has changed from cash to non-cash payments and made payments more practical, effective, efficient and simple. This study aims to determine the effect of social status, financial iteration, and digital literacy on the use of BRI mobile banking on students of Universitas Muhammadiyah Surakarta. This research is a quantitative study using a questionnaire distributed via google form as a data collection technique. The population in this study were students of the 2018-2021 accounting education study program at Universitas Muhammadiyah Surakarta. The analysis technique used was multiple linear analysis which obtained the following results: 1) social status has a positive and significant effect on the use of BRI mobile banking on students, 2) financial literacy has a positive and significant effect on the use of BRI mobile banking on students, 3) digital literacy has no positive and significant effect on the use of BRI mobile banking on students, 4) social status, financial literacy and digital literacy simultaneously have a positive and significant effect on the use of BRI mobile banking on students.